Chemically Nano-Engineered Theranostics for Phytoconstituents as Healthcare Application - Gilani, Sadaf J.; Beg, Sarwar; Kala, Chandra; Nomani, Mohammed Shivli; Mahapatra, Debarshi Kar; Imam, Syed Sarim; Taleuzzaman, Mohamad (Current Biochemical Engineering (Discontinued), 2020)
Background: Nanomedicines are capable of disease diagnosis, drug delivery, and in monitoring the therapeutic result to provide appropriate tasks towards research goals. The best therapeutic pattern can be achieved by developing a theranostic nanomedicine, which is an emerging field. It has the advantage of loading phytoconstituents as drugs and is useful for both imaging and therapeutic function. Methods: Nowadays, the design of a novel drug delivery system of the herbal constituent is usually done through the nanotechnology approach. This technique increases the biological activity and counters the puzzles associated with plant medicines. Traditional medicine integration with nanocarriers as an NDDS is very essential in the management of chronic diseases such as hypertension, diabetes, and cancer. Results: The nanotechnology combination with plant science is a green revolution with a practical approach for decreasing the therapeutic side effects. The object of the study is to review herbal nanomedicine with an enhanced therapeutic profile and less toxicity. Conclusion: The development of herbal theranostic nanoformulation is very useful for the treatment of different diseases.
Keywords: phytoconstituents